Does the Adoption of Complex Software Impact Employment Composition and the Skill Content of Occupations? Evidence from Chilean Firms - Rita K. Almeida; Ana Margarida Fernandes; Mariana Viollaz (Institute of Labor Economics (IZA), 2017)
A major concern with the rapid spread of technology is that it replaces some jobs, displacing workers. However, technology may raise firm productivity, generating more jobs. The paper contributes to this debate by exploiting a novel panel data set for Chilean firms in all sectors between 2007 and 2013. While previous studies examine the impacts of automation on the use of routine tasks by middle-educated workers, this study focuses on a measure of complex software that is typically used by more educated workers in cognitive and nonroutine tasks for client, production, and business management. The instrumental variables estimates show that in the medium run, firms' adoption of complex software affects firms' employment decisions and the skill content of occupations. The adoption of complex software reallocates employment from skilled workers to administrative and unskilled production workers. This reallocation leads to an increase in the use of routine and manual tasks and a reduction in the use of abstract tasks within firms. Interestingly, the impacts tend to be concentrated in sectors with a less educated workforce, suggesting that technology can constrain job creation for the more skilled workers there. The paper concludes that the type of technology matters for understanding the impacts of technology adoption on the labor market.
Keywords: J23; J24; J31; O33; 330; complex software; tasks; skills; employment structure; Chile